A Serological Survey of Akabane Virus Infection in Cattle in Sudan. (21st January 2014) - Elhassan, Amira M.; Mansour, Mohammed E. A.; Shamon, Awadia A. A.; El Hussein, A. M.
Abstract : A cross-sectional survey was carried out in ten states in Sudan to determine seroprevalence and to assess risk factors associated with Akabane virus (AKAV) infection in dairy herds. Serum samples were collected from a total of 361 dairy cattle and tested for antibodies against AKAV using ELISA. The prevalence rates of AKAV antibodies in cattle varied between 69.6% in Khartoum state and 3.3% in Sennar State with an overall prevalence rate of 29.4%. The prevalence rates of AKAV antibodies were significantly associated with breed being high in crossbred (39.9%;P < 0.001 ); female sex (33%;P < 0.001 ), and animals in the age group of 2-3 years old (45.3%;P < 0.001 ). Akabane virus antibodies prevalence was also highly associated with locality (P < 0.001 ); season being high in winter season (58.1%;P < 0.001 ); and animals raised under intensive management system (37%;P < 0.001 ). Among 68 cases suffering from reproductive (abortion and infertility) problems the prevalence rate of AKAV antibodies in animals with infertility problem (76.2%;P < 0.03 ) was significantly higher than in animals with abortion (48.9%). The study revealed that AKAV infection is highly prevalent in dairy cattle in Sudan and this calls for control strategy to be implemented.